Optimizing Paclitaxel Oral Absorption and Bioavailability: TPGS Co-Coating via Supercritical Anti-Solvent Fluidized Bed Technology - Zicheng Zhong; Yanling Lan; Jinxing Chen; Lu Ping; Xuchun Li; Qing Wang; Xiaodong Zhuang; Zhenwen Qiu; Tianhui Yuan; Qiupin Guo; Long Xi; Qingguo Li; et al. (MDPI AG, 2024)
Supercritical anti-solvent fluidized bed (SAS-FB) coating technology has the advantages of reducing particle size, preventing high surface energy particle aggregation, improving the dissolution performance and bioavailability of insoluble drugs. The poor solubility of Biopharmaceutics Classification System (BCS) class IV drugs poses challenges in achieving optimal bioavailability. Numerous anti-cancer drugs including paclitaxel (PTX) belong to the BCS class IV, hindering their therapeutic efficacy. To address this concern, our study explored SAS-FB technology to coat PTX with D-α-tocopherol polyethylene glycol 1000 succinate (TPGS) onto lactose. Under our optimized conditions, we achieved a PTX coating efficiency of 96.8%. Further characterization confirmed the crystalline state of PTX in the lactose surface coating by scanning electron microscopy and X-ray powder diffraction. Dissolution studies indicated that SAS-FB processed samples release over 95% of the drug within 1 min. Moreover, cell transmembrane transport assays demonstrated that SAS-FB processed PTX samples co-coated with TPGS had an enhanced PTX internalization into cells and a higher permeability coefficient compared to those without TPGS. Finally, compared to unprocessed PTX, SAS-FB (TPGS) and SAS-FB processed samples showed a 2.66- and 1.49-fold increase in oral bioavailability in vivo, respectively. Our study highlights the efficacy of SAS-FB co-coating for PTX and TPGS as a promising strategy to overcome bioavailability challenges inherent in BCS class IV drugs. Our approach holds broader implications for enhancing the performance of similarly classified medications.